Executive function predictors of science achievement in middle-school students - Varma, Keisha; Van Boekel, Martin; Aylward, Gary; Varma, Sashank (Frontiers in Psychology, 2023)
Cognitive flexibility as measured by the Wisconsin Card Sort Task (WCST) has long been associated with frontal lobe function. More recently, this construct has been associated with executive function (EF), which shares overlapping neural correlates. Here, we investigate the relationship between EF, cognitive flexibility, and science achievement in adolescents. This is important because there are fewer educational neuroscience studies of scientific reasoning than of other academically relevant forms of cognition (i.e., mathematical thinking and language understanding). Eighth grade students at a diverse middle school in the Midwestern US completed classroom-adapted measures of three EFs (shifting, inhibition, and updating) and the WCST. Science achievement was indexed by students' standardized test scores and their end-of-the-year science class grades. Among the EF measures, updating was strongly predictive of science achievement. The association between cognitive flexibility and science achievement was comparatively weaker. These findings illuminate the relationship between EF, cognitive flexibility, and science achievement. A methodological contribution was the development of paper-and-pencil based versions of standard EF and cognitive flexibility measures suitable for classroom administration. We expect these materials to help support future classroom-based studies of EF and cognitive flexibility, and whether training these abilities in adolescent learners improves their science achievement.